Developmental Anatomy in the Zonular Connection with Lens Capsule in Macaque Eye. Issue 5 (18th April 2013) - Hiraoka, Mari; Kuroda, Teiko; Inoue, Kenichi; Senoo, Haruki; Takada, Masahiko
ABSTRACT Morphological analyses of zonule conjugated with lens capsule were performed on the developmental change in eyes from the age of fetus to 7 years old of the rhesus macaques (Macaca fuscata). The zonule was filamentous network in late fetus. After birth, the zonular microfibrils originated from the nonpigmented epithelium of the ciliary process. On the extending path toward the lens capsule through the chamber, microfibril assembled with neighbor fibril and also cohered with one another forming bundle. With growth, these bundles bifurcated into anterior and posterior groups on the equatorial region of capsule. The developmental distribution of bundles in the capsule was characteristic on anterior group, that is, bifurcation into radial and circumferential extension. On the other hand, the posterior bundle undivided but radially extended within short distance from the equator. In the process of fixating with capsule, bundles untangled into fibrils and penetrated circumferentially into the superficial layer and radially into deep apical layer of the capsule. Zonule was composed fibrillin 1 microfibrils and on the extending path toward the lens capsule through the chamber, microfibril self‐assembled with neighbored fibril in composition of fascicle and also cohered with one another forming bundle. Each bundle had alternating pale and dense horizontal bands in the intracapsular extension and the stripe pattern changed in flaccid or extensive tension of zonule between capsule and process. Zonular fibril intermingled with collagen fibril of capsule with interlacing molecule of laminin. At the base of ciliary muscle, elastin‐positive connective tissue intercalated circumferentially between ciliary processes. The developmental changes of the intralamellar distribution and extension of zonule with striped pattern informed the functional role upon the elasticity in coordination with the lens capsule micromolecules. Anat Rec, 296:726–735, 2013. © 2013 Wiley Periodicals, Inc.